Acute toxicity of Zinc Oxide nanoparticles to silkworm (Bombyx mori L.). (November 2020) - Xu, Yuanyuan; Wang, Wenrong; Ma, Lin; Cui, Xianjin; Lynch, Iseult; Wu, Guohua
Abstract: Zinc Oxide nanoparticles (ZnO NPs) has been heavily used in the industry, and increasing concerns on the ecotoxicity has arisen due to the risk of release into the environment. In this work, silkworm was used here as a model organism to study the toxicity of ZnO NPs, due to the presence of a conserved immune response as well as a pharmacokinetics similar to mammals. Zn accumulation, biodistribution and toxicity in silkworms were monitored at different time points after a subcutaneous injection. The highest cumulative content of ZnO NPs was detected in the midgut. The results of catalytic activity studies confirmed that the antioxidant enzymes (SOD, CAT, GSH-PX) in midgut cells were expressed in response to ZnO NPs. The expression of genes (Dronc and Caspase-1) related to apoptosis was increased, while the Trt gene was down-regulated. A possible mechanism was proposed for toxicity of ZnO NPs to silkworms. Highlights: Silkworm was used for the acute toxicity evaluation of ZnO NPs for the first time. Midgut is the target tissue for ZnO NPs in silkworm following subcutaneous exposure. Damage to antioxidant enzymes and cell apoptosis are the mechanisms of toxicity. Silkworm is a candidate used to assess NPs toxicity and their impacts to ecosystems. Silkworms offer a good platform for investigation of mechanism of NPs toxicity.